Pengaruh NPF dan BOPO Terhadap Profitabilitas pada Bank BJB Syariah Periode 2014-2021 - Prihatin, Khristina Sri (FKIP, Universitas Banten Jaya, 2024)
This research was motivated by the acquisition of an unstable level of profitability of Bank bjb Syariah, which even experienced losses with a minus profitability. This study aims to analyze whether Non Performing Financing (NPF) and Operating Costs to Operating Income (BOPO) simultaneously affect the Profitability (ROA) of Bank bjb Syariah (2014-2021),was well was to analyze whether Non Performing Financing (NPF) and Operating Costs to Operating Income (BOPO) partially affect the profitability (ROA) of Bank bjb Syariah (2014-2021), and to analyze which factor has the most effect on profitability (ROA). This study uses a quantitative method with the sample in this study, namely the financial statements of bank bjb syariah (2014-2021), sampling using the Purposive Sampling method. The research instrument uses secondary data processed from bank bjb syariah. The results of the research that have been conducted show that the simultaneous test shows that independent variable NPF and BOPO which has a significant effect on the ROA of Bank bjb Syariah (2014-2021 period). The partial test results on the NPF variable have a significant effect on ROA, while the BOPO variable has no significant effect on ROA.